THE INFLUENCE OF SIMULATION-BASED ENGLISH COMMUNICATION TRAINING ON CONFIDENCE AND COMMUNICATION COMPETENCE OF STUDENT'S HEALTHCARE PROFESSIONALS NURSING AT UNIVERSITAS MUHAMMADIYAH PRINGSEWU - Fini widya fransiska; Esa Pratama Putra; Echa Dian Anggraini; Bella Puspita Hati; Yudiyantoro Yudiyantoro (Penelitian dan Pengembangan Ilmu, 2025)
In the context of nursing education in Indonesia, English communication skills are crucial for improving the quality of interactions between students and patients, especially in multicultural clinical settings. However, many nursing students face challenges in effectively communicating in English, which may impact the quality of healthcare services. This study aims to analyze the influence of simulation-based English communication training on the confidence and communication competence of nursing students at Universitas Muhammadiyah Pringsewu. The sample consisted of students selected through purposive sampling. Data were collected using questionnaires adapted from self-confidence and communication competence scales and analyzed using simple linear regression. The results of the analysis indicate that simulation-based training significantly enhances students’ confidence and communication competence, showing a positive impact on their ability to interact in clinical environments. These findings underscore the importance of integrating simulation-based communication training into the nursing education curriculum to improve students' communication skills, thereby contributing to the overall quality of healthcare services in Indonesia.